The Secret of Dates in the Perspective of Hadith (Convergence with Science in Health Sciences) - Alfi Salwa Qibty (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the Hadith on the secret of the dates in the perspective of the hadith. This research uses a qualitative approach by interpreting the Hadith text, by applying the analytical descriptive method through the Syarah Hadith method and correlating its account through science. Regarding the formal objects in which it is related to the study of hadiths, while for the obese mechanical is the Hadith about the secret of the dates in the perspective of the hadith. The context related to this research is relevant to science and technology in current health science. The results and discussion of this study indicate that the quality of Hadith History of Tirmidzi No. 594 Hasan Shahih said, which met the quantification of Maqbul's hadith for the disclosure of Islam. This study concludes that the downturn of the hadith and science in health science is associated with the secret of the tues teaching the values of affection in its relevance to grace and the salchanctions in Islam.